UJI KEBERFUNGSIAN DIFERENSIAL RASCH PADA SKALA PERSEPSI TERHADAP POLITIK IDENTITAS KELAS MENENGAH MUSLIM - Lucky Purwantini; Ainur Rofieq (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2020)
The emergence of the 411 and 212 Defend Islamic Action movements in the election for the Governor of DKI Jakarta indicates the rise of identity politics. Interestingly, all of these movements are dominated by the Muslim middle class who are politically apolitical, conservative on religious values, but also part of a consumerist society, so the question of this research is how the perception of the Muslim middle class towards identity politics is associated with the emergence of the Action movement. Defend Islam 411 and 212. To understand the formation of identity politics, according to Buchari there are three ways, namely: legitimate identity, resistant identity, and project identity. The data was collected using a scale of perceptions of identity politics in the Muslim middle class and analyzed using the Rasch model. The Differential Functioning Test (DIF) is used to detect bias in items. The DIF results show that 9 items on the perception politics of identity scale have no bias towards both men and women. In addition, the DIF results also show that the 9 items of the perception scale on identity politics also do not have a bias either on subjects who are members of religious organizations or who are not members of religious organizations.